INFLUENCE OF CUSTOMER EXPERIENCE AND SERVICE QUALITY TOWARDS CUSTOMER LOYALTY WITH CUSTOMER SATISFACTIONAS AN INTERVERNING VARIABLE AT ACE HARDWARE JUANDA MEDAN - Nadya Nurul Sabrina; Paham Ginting; Amlys Syahputra Silalahi (RADJA PUBLIKA, 2023)
One retail company that is popular with consumers in the field of household equipment and furniture is Ace Hardware. This research aims to determine and analyze the influence of customer experience and service quality on customer loyalty through customer satisfaction as an intervening variable at ACE Hardware Juanda Medan. The population in this study are the people of Medan City who have visited at least 2 times with an unknown number. The sampling technique in this research was nonprobability sampling of 100 respondents. The data analysis method uses Structural Equation Modeling-Partial Least Squares (SEM-PLS). The research results show that customer experience influences customer loyalty. Service quality has a negative effect on customer loyalty. Customer experience influences customer satisfaction. Service quality influences customer satisfaction. Customer satisfaction influences customer loyalty. Customer experience influences customer loyalty through customer satisfaction as an intervening variable. Service quality influences customer loyalty through customer satisfaction as an intervening variable.